2019
DOI: 10.1111/jgs.16187
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Elevated C‐Reactive Protein Among US Older Adults

Abstract: OBJECTIVES: To investigate racial differences in elevated C-reactive protein (CRP) and the potential factors contributing to these differences in US older men and women. DESIGN: Nationally representative cohort study. SETTING: Health and Retirement Study, 2006 to 2014. PARTICIPANTS: Noninstitutionalized non-Hispanic black and white older adults living in the United States (n = 13 517). MEASUREMENTS: CRP was categorized as elevated (>3.0 mg/L) and nonelevated (≤3.0 mg/L) as the primary outcome. Measures for dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
(103 reference statements)
2
13
0
1
Order By: Relevance
“…We also observed that a higher proportion of Black/AA patients had CRP ≥5.1 mg/L at post-RT (58%). This is consistent with the previous ndings that higher CRP levels were reported in Black/AA patients compared to whites, Chinese, or Japanese [35,36]. Multiple genetic and environmental factors may contribute to racial/ethnic differences in CRP levels.…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that a higher proportion of Black/AA patients had CRP ≥5.1 mg/L at post-RT (58%). This is consistent with the previous ndings that higher CRP levels were reported in Black/AA patients compared to whites, Chinese, or Japanese [35,36]. Multiple genetic and environmental factors may contribute to racial/ethnic differences in CRP levels.…”
Section: Discussionsupporting
confidence: 93%
“…A recent review posited that observed racial and ethnic differences in COVID-19 outcomes may arise from a differential inflammatory response between groups, driven by underlying differences in chronic inflammation from different burdens of co-morbidity, socio-economic factors, genetic factors, and psychologic stressors 25 . Differences in chronic inflammation as measured by CRP levels have been previously described, with several studies finding that Black patients have higher median CRP levels than White patients, though these differences were heavily attenuated after accounting for differences in comorbidities and psychosocial factors 26 , 27 . Similarly, after adjusting for cardiovascular and COVID-19 risk factors, Black race compared to non-Black was associated with relatively lower levels of CRP and suPAR, reflecting perhaps an attenuated inflammatory response to SARS-CoV-2 infection and leading to similar survival rates compared to non-Black patients despite their significantly higher burden of co-morbidities.…”
Section: Discussionmentioning
confidence: 80%
“…As social support is an important mediator in the literature, and to ensure the role of positive social support was truly not important in explaining TL, we re-screened our final models of demographic and health variables, but found further evidence of social support being a confounder, so those results are not reported. Models 2, 3, 6 and 7 also add categorical measures of hs-CRP (mg/dL), the only inflammatory biomarker available from the same year of data when TL was collected: a binary measure of high hs-CRP (≤ 3 vs. > 3 and < 10 44 ) in Models 2 and 6, and a tri-level measure of hs-CRP (< 1, 1–3, > 3 and < 10 17 ) in Models 3 and 7.…”
Section: Methodsmentioning
confidence: 99%